A constricted mitochondrial morphology formed during respiration - Manish K. Singh; Laetitia Cavellini; Maria Angeles Morcillo-Parra; Christina Kunz; Mickaël Lelek; Perrine Bomme; Aurélia Barascu; Cynthia Alsayyah; Maria Teresa Teixeira; Naïma Belgareh-Touzé; Adeline Mallet; Lea Dietrich; et al. (Nature Communications)
Abstract Mitochondria assemble in a dynamic tubular network. Their morphology is governed by mitochondrial fusion and fission, which regulate most mitochondrial functions including oxidative phosphorylation. Yet, the link between mitochondrial morphology and respiratgion remains unclear. Here, we uncover a mitochondrial morphology dedicated to respiratory growth of Saccharomyces cerevisiae, which we refer to as “Ringo”. The Ringo morphology is characterized by stable constrictions of mitochondrial tubules. Ringo constrictions are mediated by the yeast dynamin Dnm1 and, unlike mitochondrial fission, occur in the absence of contacts with the endoplasmic reticulum. Our data show that blocking formation of the Ringo morphology correlates with decreased respiration, decreased expression of OXPHOS subunits and perturbed mitochondrial DNA distribution. These results open important perspectives about the link between mitochondrial form and function.